2019
DOI: 10.1186/s12951-019-0551-6
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of microglia-derived extracellular vesicles: towards miRNA signatures and neuroprotection

Abstract: The functional preservation of the central nervous system (CNS) is based on the neuronal plasticity and survival. In this context, the neuroinflammatory state plays a key role and involves the microglial cells, the CNS-resident macrophages. In order to better understand the microglial contribution to the neuroprotection, microglia-derived extracellular vesicles (EVs) were isolated and molecularly characterized to be then studied in neurite outgrowth assays. The EVs, mainly composed of exosomes and microparticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 68 publications
0
36
0
1
Order By: Relevance
“…Hence, Prada et al (2018) found miR-146a, a miRNA associated to several inflammation-related diseases, to be enriched in microglia-derived EVs. This finding was later confirmed by a study of Lemaire et al (2019) . As CNS sentinels, microglia are also responsible for the overall homeostasis of the brain: they are able to sense extracellular ATP, which may be the result of damaged cells, and to react to these high ATP levels by shedding EVs containing pro-inflammatory factors, like IL-1β, thus enhancing neuroinflammation ( Bianco et al, 2005 ).…”
Section: Physiological Role Of Evs In the Cnsmentioning
confidence: 52%
“…Hence, Prada et al (2018) found miR-146a, a miRNA associated to several inflammation-related diseases, to be enriched in microglia-derived EVs. This finding was later confirmed by a study of Lemaire et al (2019) . As CNS sentinels, microglia are also responsible for the overall homeostasis of the brain: they are able to sense extracellular ATP, which may be the result of damaged cells, and to react to these high ATP levels by shedding EVs containing pro-inflammatory factors, like IL-1β, thus enhancing neuroinflammation ( Bianco et al, 2005 ).…”
Section: Physiological Role Of Evs In the Cnsmentioning
confidence: 52%
“…Interestingly, leech microglia EVs have been described to trigger a significant increase of rat PC12 cell differentiation, suggesting the presence of common molecular mediators and the evolutionary conservation of EV-mediated communication systems (Raffo-Romero et al, 2018). In addition, a proteomic analysis and studies on miRNA signatures of EVs released from leech microglia further support the presence of conserved neuroprotective cargo throughout the evolution (Arab et al, 2019;Lemaire et al, 2019).…”
Section: Extracellular Vesicles In the Central Nervous Systemmentioning
confidence: 92%
“…Exosomes derived from microglia upon toxic exposure to alcohol promote C1q mediated neuronal cell death [ 154 ]. Interestingly, a recent report demonstrated that the glia–neuron communication mediated by EVs is maintained even between species [ 155 ]. The authors isolated exosomes from leach microglial cells and observed an increase in neurite outgrowth in rat primary neurons [ 155 ].…”
Section: Microglial Exosomes In Neurodegenerationmentioning
confidence: 99%